What is the average rate of change between f (1) and f (5) in the function f (x) = x2 – x – 6 ?

Question

What is the average rate of change between f (1) and f (5) in the function f (x) = x2 – x – 6 ?

in progress 0
Calantha 3 weeks 2021-08-26T18:02:55+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-26T18:04:42+00:00

    Answer:

    { \tt{average =  \frac{f(1) + f(5)}{2} }} \\  \\  = { \tt{ \frac{( {1}^{2}  - 1 - 6) + ( {5}^{2} - 5 - 6) }{2} }} \\  =  \frac{ - 6 + 14}{2}  \\  \\  = { \tt{4}}

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )